2023
DOI: 10.1038/s41467-023-35848-y
|View full text |Cite
|
Sign up to set email alerts
|

Self-vectoring electromagnetic soft robots with high operational dimensionality

Abstract: Soft robots capable of flexible deformations and agile locomotion similar to biological systems are highly desirable for promising applications, including safe human-robot interactions and biomedical engineering. Their achievable degree of freedom and motional deftness are limited by the actuation modes and controllable dimensions of constituent soft actuators. Here, we report self-vectoring electromagnetic soft robots (SESRs) to offer new operational dimensionality via actively and instantly adjusting and syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 40 publications
(50 reference statements)
0
9
0
Order By: Relevance
“…7M), thereby realizing omnidirectional motion with one actuator. 123 However, they can only move within a very small range due to the demand for magnetic fields. Ye et al proposed integrating magnetic fields to simulate the movement of jellyfish, as shown in Fig.…”
Section: Lm Actuators Applied In Soft Roboticsmentioning
confidence: 99%
“…7M), thereby realizing omnidirectional motion with one actuator. 123 However, they can only move within a very small range due to the demand for magnetic fields. Ye et al proposed integrating magnetic fields to simulate the movement of jellyfish, as shown in Fig.…”
Section: Lm Actuators Applied In Soft Roboticsmentioning
confidence: 99%
“…designed a self-vectoring electromagnetic soft robot. Modularization and recombination of magnetron-based micro-regions allowed for diverse motions, including expanding rotation, left-right rocking, left-right flipping, and continuous rolling, achieved by applying different current signals [ 93 ]. This work demonstrates the multimodal motion of a soft robot through a combination of actuation methods and modularity.…”
Section: Strategies For Soft Actuationmentioning
confidence: 99%
“…Different from conventional robots, which depend comprehensively on direct-current or alternating-current motor drive systems and complex assembly components, microrobots are usually in the size of micrometers and are generally made based on relatively simple materials but ingenious structural designs [27,[244][245][246]. FsLDW technology can process and integrate various intelligent materials in an effective and flexible manner, enabling preparation of microrobots with more complex geometric shapes and advanced functionalities, which has aroused widespread interest in the scientific community [99,174,178,247].…”
Section: Microroboticsmentioning
confidence: 99%